Retail Employees’ Job Hopping: The Roles of Exhaustion, Satisfaction, and Support - Syahputra, Moch Ihsan; Kadiyono, Anissa Lestari; Sulastiana, Marina (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Retail employee mobility is increasing in emerging labor markets. This study advances turnover theory by integrating perceived organizational support, emotional exhaustion, and job satisfaction within a single structural model to explain job hopping intention rather than general turnover intention. Using a quantitative explanatory design, data from 458 retail employees in South Sulawesi were analyzed with SEM in Jamovi. The findings reveal that emotional exhaustion significantly increases job hopping intention, while job satisfaction reduces it, whereas perceived organizational support shows no direct effect. These results indicate that psychological strain and affective evaluation of work are more decisive than formal support mechanisms in shaping mobility decisions. Managerially, retail firms should prioritize emotional well-being, workload balance, and job satisfaction to reduce excessive employee mobility and sustain workforce stability.